Support from Grandparents to Families with Infants - WILLIAMS, JAMES; MURRAY, AISLING; QUAIL, AMANDA (ESRI, 2011)
Parent-child interactions are influenced by factors outside the immediate family. A recent paper based on data from the Growing Up in Ireland study (GUI) focuses in particular on the support provided by grandparents in caring for very young children. Such support can have important direct and indirect influences on child development. For example, a grandparent who babysits a young child while parents have a night out has a direct interaction with the child in the context of providing care. However, there is also an indirect influence in the context of supporting the mother-father relationship which, in turn, could be expected to affect (positively) parental interactions with the child.
PUBLISHED
Dublin
Keywords: Social Policy; Child care; Grandparents